2016
DOI: 10.1021/acs.jproteome.6b00578
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of the Lysine Succinylome in Candida albicans

Abstract: Candida albicans is the most common human fungal pathogen for both immunocompetent and immunocompromised individuals. Lysine succinylation is a frequently occurring post-translational modification that is found in many organisms; however, the role of succinylation is still under investigation. Here, we initiated a first screening of lysine succinylation in C. albicans. We identified 1550 succinylation sites from 389 proteins in C. albicans, demonstrating that succinylation is conservative in this organism. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 36 publications
3
24
0
Order By: Relevance
“…Results from this study show that Ksuc sites are present in RagB, FimA (major subunit protein of the FimA fimbriae), Mfa1 (major subunit protein of the Mfa1 fimbriae), RgpA, RgpB, Kgp, and PorR (involved in A‐LPS biosynthesis). Given that Ksuc can change protein structure and function, the data from this study support the hypothesis that this modification is involved in the virulence of P gingivalis , similar to its role in other pathogenic bacteria or fungi …”
Section: Resultssupporting
confidence: 76%
“…Results from this study show that Ksuc sites are present in RagB, FimA (major subunit protein of the FimA fimbriae), Mfa1 (major subunit protein of the Mfa1 fimbriae), RgpA, RgpB, Kgp, and PorR (involved in A‐LPS biosynthesis). Given that Ksuc can change protein structure and function, the data from this study support the hypothesis that this modification is involved in the virulence of P gingivalis , similar to its role in other pathogenic bacteria or fungi …”
Section: Resultssupporting
confidence: 76%
“…4b and Additional file 2: Table S4). These observations are consistent with the previous results in T. aestivum [7] and C. albicans [12]. Cellular component analysis revealed that succinylproteins were mainly distributed in cells (39.5%), macromolecular complexes (25.7%), organelles (24.5%) and membranes (7.5%) (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Therefore, proteins with K or R in corresponding sites are more easily to be the preferred substrates of lysine succinyltransferase in G. lucidum . It is noteworthy that the conserved motifs form strawberry stigmata [11], common wheat [7], C. albicans [12], and V. parahemolyticus [14] are different, indicating that different species contain unique succinylated proteins with specific functions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Image‐guided fluorogenic tracking of H 2 PO 4 − and CN − ions was demonstrated in Candida albicans (C.A), which are well‐known virulent primitive eukaryotic cells that typically resemble eukaryotic cells . Experiments were performed in C.A species considering the simplicity in culturing, cost effectiveness, and easier handling as compared to animal cells.…”
Section: Resultsmentioning
confidence: 99%